2018
DOI: 10.1155/2018/6921845
|View full text |Cite
|
Sign up to set email alerts
|

A Sargassum fluitans Borgesen Ethanol Extract Exhibits a Hepatoprotective Effect In Vivo in Acute and Chronic Liver Damage Models

Abstract: One of the leading causes of death worldwide, cirrhosis, is a liver condition characterized by chronic necrosis, inflammation, and fibrosis. Hepatoprotective compounds, such as antioxidants, can prevent fibrosis. Macroalgae (seaweed) contain high amounts of antioxidant compounds and are plentiful; indeed, species such as Sargassum fluitans Borgesen (Phaeophyceae) carpet many beaches in the Caribbean Basin. An in vivo assay was done evaluating the possible hepatoprotective effect of a Sargassum fluitans ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Hepatoprotection has been reported with the administration of Turbinaria decurrens fucoidan, which ameliorates antioxidant status and decreases lipid peroxidation marker levels [73]. Administration of 50 mg/kg Sargassum fluitans ethanol extract reduced the levels of APAP − and CCl 4 − in liver damage models through the inhibition of inflammation and fibrosis in liver tissue [32]. This result is in accordance with the research on the hepatoprotective effects of Myagropsis myagroides, Sargassum henslowianum, and Sargassum siliquastrum [152].…”
Section: Sulfated Polysaccharidesupporting
confidence: 78%
See 1 more Smart Citation
“…Hepatoprotection has been reported with the administration of Turbinaria decurrens fucoidan, which ameliorates antioxidant status and decreases lipid peroxidation marker levels [73]. Administration of 50 mg/kg Sargassum fluitans ethanol extract reduced the levels of APAP − and CCl 4 − in liver damage models through the inhibition of inflammation and fibrosis in liver tissue [32]. This result is in accordance with the research on the hepatoprotective effects of Myagropsis myagroides, Sargassum henslowianum, and Sargassum siliquastrum [152].…”
Section: Sulfated Polysaccharidesupporting
confidence: 78%
“…Several studies have revealed that dietary habits and traditional culture in consuming seaweed in Asian countries, especially in Japan and Korea, are correlated with a lower incidence of chronic diseases such as cancer, cardiovascular disease, hypertension, osteoporosis, and obesity [6,[23][24][25][26][27]. Several studies have also revealed that consumption of seaweed can reduce the occurrence of chronic pathologies, including neurodegenerative diseases [28], cardiovascular disease [29], obesity [30], diabetes [14], cancer [31], liver disease [32], osteoporosis [33], and arthritis [34]. Furthermore, collaborative cohort studies have been conducted to investigate the effect of the seaweed diet in Japan and Korea, and the results of these studies showed that seaweed-containing diets are related to protection against cancer (Iso and Kubota 2007; Kim et al 2020c).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocytes are the primary part that manages different metabolic actions of the liver. Alteration of this organ will result in disorder of metabolic function of the body . Unintended high dosage administration of CCl 4 can be a consequence for liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocytes are the primary part that manages different metabolic actions of the liver. Alteration of this organ will result in 10,[28][29][30] Unintended high dosage administration of CCl 4 can be a consequence for liver injury. The advancement of CCl 4 -actuated hepatotoxicity appears to depend mostly on the presence of free radicals and oxidative processes.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic liver disease can induce many complications, and it has become a major contributor to high morbidity and mortality rates [1]. Moreover, the World Health Organization has reported that approximately 2.3 million people suffer from liver diseases each year [2]. The liver, the most important metabolic and detoxification organ against various endogenous and exogenous harmful substances, is sensitive to environmental toxins and easily damaged by chemicals such as carbon tetrachloride (CCl 4 ) [3].…”
Section: Introductionmentioning
confidence: 99%